Allele mining in the Argentine public maize inbred line collection of two paralogous genes encoding NAC domains - Estermann, M.A.; Ugarte, A.; Pretini, Nicole; Vega, Claudia Rosa Cecilia; Olmos, Sofía Eugenia (Springer Nature, 2023)
NAC proteins are plant transcription factors involved in biotic and abiotic stress responses, with conserved sub-domain motifs. To our knowledge, no diversity studies have been carried out at the nucleotide level of candidate NAC genes of crops. Here, we investigated allele diversity and putative protein-coding sequences in two paralogous maize NAC genes, GRMZM2G179885 and GRMZM2G347043. The GRMZM2G179885 gene is the closest ortholog of WNAC-B1, responsible for enhancing nitrogen remobilization and senescence in wheat. The GRMZM2G347043 gene is the homolog to the characterized ZmSNAC1 allele, which promotes the dehydration tolerance response in Arabidopsis. Nucleotide diversity for both genes was determined in a core set of the Argentine public maize collection of temperate inbred lines structured in four diverse subpopulations. The frequency of nucleotide changes at both exons and introns of GRMZM2G179885 and GRMZM2G347043 was lower (1/137 bp-1/83 bp and 1/472 bp-1/51 bp, respectively) than that of other maize genes. Tajima’s D values were non-significant, indicating the absence of selection at these genes. The five sub-domains of NAC proteins were predicted at both genes, thus implying: (i) high conservation of these two genes at the genomic level, and (ii) scarce divergence between GRMZM2G179885 and GRMZM2G347043 protein-coding sequences, which confirms their relationships as ancestral paralogs. Although the functional activity of both genes in maize metabolism is still unclear, our findings contribute to demonstrating that their NAC proteins are common alleles and would serve as a source for abiotic stress improvement in the Argentine public maize inbred line collection.